The Influence of SIPD Applications, Human Resources, Internal Control on the Reliability of Financial Reports with Accountability of Agency Performance as a Moderating Variable (Case Study of South Sumatra Provincial Government) - Herdanita, Fessy Angela Herdanita; Sartika, Dewi; Jaya, Ade Kemala (LPPM Universitas Pelita Bangsa, 2025)
This study aims to analyze the effect of good corporate governance and company performance on firm value which can be used as a management reference in using good and appropriate governance so that it can benefit the company as a whole. The population in this study used all companies listed on the Indonesia Stock Exchange with a sample of state- owned companies in 2016-2019. The variables used in this study are independent board of commissioners, institutional ownership, audit committee and Return on Equity (ROE), while the firm value variable is proxied by Price Book Value (PBV). The technique used in sampling in this study is to use purposive sampling technique. The type of research used is explanatory research with a quantitative approach. ased on the analysis, the results show that partially, the independent board of commissioners and ROE have a positive and significant effect on firm value, institutional ownership has a negative and significant effect on firm value, the audit committee has no and no significant effect on firm value, simultaneously independent board of commissioners, institutional ownership , audit committee and ROE affect firm valuThis research aims to analyze the influence of SIPD applications, human resources, internal control on the reliability of financial reports with agency performance accountability as a moderating variable (case study of the South Sumatra Provincial Government). This research discusses human resources using the SIPD application to ensure transparency, accuracy and accountability in fund management. By using a quantitative approach with a survey design measured numerically, allowing in-depth statistical analysis to answer research questions. With a total sample size of this research, 160 per 4 people in the Finance Section of each SKPD as respondents. The results of the research show that the SIPD application has a significant influence on the reliability of financial reports, human resources has an influence but is not significant on the reliability of financial reports, internal control has an influence but is not significant on the reliability of financial reports, the SIPD application and the reliability of financial reports have a significant influence on moderating the accountability of agency performance, human resources have an insignificant influence and internal control has a significant influence on the reliability of financial reports with accountability of agency performancee.